Proposta de curso a distância sobre metodologias ativas de ensino para preceptores da graduação em Farmácia - Moura Filho, Severino Alves de (2021)
Considering the importance of training and continuing education for preceptor pharmacists, as fundamental strategies in the construction of a dynamic and effective teaching-learning model, in compliance with the National Curriculum Guidelines for the undergraduate course in Pharmacy and its pedagogical proposal, a distance training program was created. for the preceptors of the Pharmacy Course at the Federal University of Rio Grande do Norte on active teaching methodologies in health, in order to raise awareness and encourage the implementation of these methodologies during practical activities in the various scenarios of pharmaceutical teaching. This is a methodological research carried out in three stages: 1) Situational Diagnosis; 2) Literature review study; and 3) Construction of the training course for preceptors. The survey included the submission of 104 electronic forms through Google forms, with the acceptance of 43 preceptors to participate in the survey, these mostly female (72.1%) and with a specialist title (46.6%), average age of 38.1 years and with professional experience between 11 to 20 years (51.2%). With regard to training to exercise preceptorship, 36 (83.7%) never received training and in 100% of the cases the insertion as preceptors occurred casually, due to the professional working in environments that are part of the internship field of the pharmacy course. In the analysis of the preceptors' difficulties and potentials, the taste for teaching, motivation for student learning was pointed out as positive points. Among the difficulties are the work overload (time), physical space, moments to exchange knowledge and lack of training. These findings corroborate the literature review stage, which revealed that the theme of teaching methodologies in preceptorship in Pharmacy is still a gap to be explored. Therefore, a proposal for a distance course on active health teaching methodologies was elaborated in order to present various available methods that preceptors can use with students during practice, in different scenarios. Contributing to adequate pedagogical skills and teaching learning that promotes the development of criticalreflective training for students.